Theories of Translation - Williams, J. author. aut Link
IX, 145 p.
Keywords: Presents the most important theories in Translation Studies that have emerged over the last 50 years. Particularly innovative is the inclusion of theories from outside North America and Europe, theoretical perspectives on recent technological developments and a consideration of the nature of theory in the field.